47.5k views
4 votes
How do you do this question?

How do you do this question?-example-1
User WenChao
by
4.4k points

1 Answer

0 votes

Answer:

-1

Explanation:

dy/dt = y² − 1 = (y + 1) (y − 1)

At t = 0, y = 0, and dy/dt = -1. Therefore, y is initially decreasing.

As y decreases, dy/dt increases. When y = -1, dy/dt = 0 and changes signs from negative to positive.

As y increases above -1, dy/dt again becomes negative. So y continues to approach -1 as t approaches infinity.

User Marcogomesr
by
4.6k points